2005
DOI: 10.1038/sj.bjp.0706122
|View full text |Cite
|
Sign up to set email alerts
|

Neuritic regeneration and synaptic reconstruction induced by withanolide A

Abstract: 1 We investigated whether withanolide A (WL-A), isolated from the Indian herbal drug Ashwagandha (root of Withania somnifera), could regenerate neurites and reconstruct synapses in severely damaged neurons. We also investigated the effect of WL-A on memory-deficient mice showing neuronal atrophy and synaptic loss in the brain. Axons, dendrites, presynapses, and postsynapses were visualized by immunostaining for phosphorylated neurofilament-H (NF-H), microtubule-associated protein 2 (MAP2), synaptophysin, and p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
198
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 285 publications
(204 citation statements)
references
References 43 publications
6
198
0
Order By: Relevance
“…The intensity of peak was estimated by ImageJ software; values are summarized in Table 2. WF A, WN A, WS V, WNN, and 1,2-DWM are biologically active, and among all these, WF A and WN A are potent [38][39][40][41][42][43][44][45]; from the present study, we also observed the same results. WF A has the highest antioxidant activity followed by WN B, WN A, WS V, 1,2-DWM, and WNN, respectively, while in unknown components, peak No.…”
Section: Resultssupporting
confidence: 85%
“…The intensity of peak was estimated by ImageJ software; values are summarized in Table 2. WF A, WN A, WS V, WNN, and 1,2-DWM are biologically active, and among all these, WF A and WN A are potent [38][39][40][41][42][43][44][45]; from the present study, we also observed the same results. WF A has the highest antioxidant activity followed by WN B, WN A, WS V, 1,2-DWM, and WNN, respectively, while in unknown components, peak No.…”
Section: Resultssupporting
confidence: 85%
“…Withanoside IV (31) and VI (32) predominantly induced dendritic outgrowth in normal cortical neurons, while withanolide A (504) predominantly induced axon outgrowth (262). These withanolides also showed neuritic regeneration and synaptic reconstruction of damaged cortical neurons and prevented both dendritic and axonal atrophy induced by Ab (25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35) (261,263). Oral administration of withanoside IV significantly improved memory deficit in Ab(25-35) treated mice, and sominone, the aglycone of withanoside IV, was shown to be the major metabolite after administration.…”
Section: Synaptogenesis and Neuritic Outgrowthmentioning
confidence: 99%
“…WS root extract and withanoside VI were shown to possess inhibitory action on acetylcholinesterase activity in both in vivo and in vitro (Choudhary et al 2005). Further, evidences suggest the protective effect of WS root extract and its constituents on presynaptic and post-synaptic neurons in animal models of dementia and spinal cord injury (Kuboyama et al 2005). A polyherbal preparation, BR-16 (Mentat®), which includes WS as one of the major component exhibited significant protective effect against reserpine-induced catalepsy in mice (Kumar and Kulkarni 2006).…”
mentioning
confidence: 99%